Foodborne hazards in food in Burkina Faso, 1990–2019: a systematic review and meta-analysis - Dinede, Getachew; Amenu, Kebede; Alonso, Silvia; Gazu, Lina; Mutua, Florence; Roesel, Kristina; Lindahl, Johanna F.; Sousa, Filipe Maximiano; Ulrich, Pattama; Guadu, Tadesse; Dione, Michel; Ilboudo, Guy; et al. (Frontiers in Sustainable Food Systems, 2023)
Background: Foodborne diseases impose substantial public health burden and jeopardize socioeconomic development worldwide. While accurate information on foodborne hazards is needed for informed decision in food safety interventions, such information is scarce in developing countries such as Burkina Faso. We conducted a systematic review and meta-analysis of studies reporting foodborne hazards in foods in Burkina Faso to describe the present knowledge of the situation.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)